The Taiji Model of Self II: Developing Self Models and Self-Cultivation Theories Based on the Chinese Cultural Traditions of Taoism and Buddhism - Wang, Zhen-Dong; Wang, Feng-Yan (Frontiers in Psychology, 2020)
Based on the construction of the “Taiji Model of Confucian Self” that aims to explain self-structure, the progression of self-cultivation and the dominion of person-making in the context of Chinese Confucian culture, according to the ideas of Taoism and Buddhism, the present study develops the “Taiji Model of Taoist Self” and the “Taiji Model of Buddhist Self” and identifies four realms of Taoist self-cultivation and five realms of Buddhist self-cultivation. In light of the Taiji Model of Taoist Self, self-structure can be divided into the soft self (the Yin part) and the hard self (the Yang part). The Taiji Model of Taoist Self splits the process of self-cultivation into four realms: suren (vulgarian), xianren (solon), shengren (saint), and zhenren (immortal). The Taiji Model of Buddhist Self splits self-structure into the dusty self (the Yin part) and the pure self (the Yang part) and divides the process of self-cultivation into five realms: Humans and Heaven, Arhat, Pratyekabuddha, Bodhisattva, and Buddha.